2014
DOI: 10.1016/j.bjp.2014.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Chemical diversity and antileishmanial activity of crude extracts of Laurencia complex (Ceramiales, Rhodophyta) from Brazil

Abstract: A B S T R A C TChemical profiles of extracts of four species from Laurencia complex (Ceramiales, Rhodophyta) from different populations collected along Southeast Brazilian coast were assessed by High Performance Liquid Chromatography coupled with a Diode Array Detector in order to observe geographic chemical variability. Aiming to evaluate the impact of chemical diversity on potential pharmaceutical uses, the extracts were tested against the promastigote form of Leishmania amazonensis. The most active extracts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The distinct larvicidal activities observed suggest the existence of qualitative and/or quantitative differences in metabolite content between locations [ 46 , 47 , 48 ]. Further GC-MS analysis revealed that both extracts displayed the same major compounds.…”
Section: Resultsmentioning
confidence: 99%
“…The distinct larvicidal activities observed suggest the existence of qualitative and/or quantitative differences in metabolite content between locations [ 46 , 47 , 48 ]. Further GC-MS analysis revealed that both extracts displayed the same major compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Among all marine macroalgae, the red algae of the genus Laurencia are accepted unanimously as a prolific producer of secondary metabolites, highlighting the sesquiterpenes, diterpenes, triterpenes and C15 acetogenins [22,23]. Many compounds of Laurencia exhibit important antiparasitic properties against several parasites [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…highlighting the sesquiterpenes, diterpenes, triterpenes and C15 acetogenins [ Many compounds of Laurencia exhibit important antiparasitic properties against s parasites [24][25][26][27][28][29] The sesquiterpenes isolated from the genus Laurencia currently constitute mor 575 structures reported. Among them, the chamigrane-type sesquiterpenes are the frequently occurring class, accounting for approximately 30% of all isolated sesq penes.…”
Section: Introductionmentioning
confidence: 99%